1999
DOI: 10.1139/z98-195
|View full text |Cite
|
Sign up to set email alerts
|

The importance of meat, particularly salmon, to body size, population productivity, and conservation of North American brown bears

Abstract: We hypothesized that the relative availability of meat, indicated by contribution to the diet, would be positively related to body size and population productivity of North American brown, or grizzly, bears (Ursus arctos). Dietary contributions of plant matter and meat derived from both terrestrial and marine sources were quantified by stable-isotope analysis (δ13C and δ15N) of hair samples from 13 brown bear populations. Estimates of adult female body mass, mean litter size, and population density were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(86 citation statements)
references
References 24 publications
2
83
1
Order By: Relevance
“…The femur lengths of males at the subpopulation level were positively correlated with the ␦ 15 N values, and because ␦ 15 N values are higher at the predator trophic level (DeNiro and Epstein 1981;Minagawa and Wada 1984), the mean skeletal size of the male bear subpopulations was strongly correlated with their trophic status, which is consistent with other studies from North America (Hilderbrand et al 1999;Mowat and Heard 2006). The result suggests that the body size of male bears is adapted to regional nutrient availability over several generations but not within a generation, and the geographical variation in diets causes the geographical variation in the body size of brown bear subpopulations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The femur lengths of males at the subpopulation level were positively correlated with the ␦ 15 N values, and because ␦ 15 N values are higher at the predator trophic level (DeNiro and Epstein 1981;Minagawa and Wada 1984), the mean skeletal size of the male bear subpopulations was strongly correlated with their trophic status, which is consistent with other studies from North America (Hilderbrand et al 1999;Mowat and Heard 2006). The result suggests that the body size of male bears is adapted to regional nutrient availability over several generations but not within a generation, and the geographical variation in diets causes the geographical variation in the body size of brown bear subpopulations.…”
Section: Discussionsupporting
confidence: 90%
“…female body size remains inconclusive. A larger body size also increases the reproductive success of female bears (Stringham 1990;Hilderbrand et al 1999;Zedrosser et al 2007), but a larger size is not always adaptive for females due to the important role of caring for the offspring. Because female bears with cubs sometimes face the risk of infanticide by male bears (Dahle and Swenson 2003;Ben-David et al 2004;McLellan 2005), larger females should be better at defending their offspring, as they are likely stronger than small females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, as salmon continue to colonize streams in Glacier Bay (Milner et al, 2007), they may become an important seasonal food for wolves, as demonstrated in coastal British Columbia (Darimont et al, 2008), other areas of Southeast Alaska (Szepanski et al, 1999), and interior Alaska (Adams et al, 2010). In our study, it is likely that scat analysis resulted in an underrepresentation of salmon in wolf diets not only because these fish are highly digestible (Hilderbrand et al, 1999), but also because scat collection occurred before the peak of spawning season. Thus, wolf use of salmon may have been greater than suggested by our results.…”
Section: Discussionmentioning
confidence: 80%